2015
DOI: 10.1108/jstpm-05-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the development of e-government using a citizen-centric approach

Abstract: Purpose – The purpose of this paper is to study the factors affecting the development of e-government by using a citizen-centric approach. Design/methodology/approach – This paper is a mixed-methods study consisting of qualitative and quantitative research. Data were collected from government agencies using a structured interview and questionnaire about e-government services. The research was collected from the people responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Despite plenty of E-Governance advantages, the existence of E-Governance services hold no meaning if these have little or no citizens’ or end users’ adoption (Trang, 2018). For successful development of E-Governance, it is necessary to create the awareness of its benefits among the nation citizenry whereby people should recognize that E-Governance is going to be helpful for them in their everyday life (Sorn-in et al , 2015), which will enhance citizens’ involvement and attitude toward E-Governance (Joseph and Plessis, 2015). To actually ensure adoption of E-Governance benefits at the bottom of the pyramid, powerful marketing is very crucial which would ensure the ultimate use of facilities created, by the citizens (GoI, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite plenty of E-Governance advantages, the existence of E-Governance services hold no meaning if these have little or no citizens’ or end users’ adoption (Trang, 2018). For successful development of E-Governance, it is necessary to create the awareness of its benefits among the nation citizenry whereby people should recognize that E-Governance is going to be helpful for them in their everyday life (Sorn-in et al , 2015), which will enhance citizens’ involvement and attitude toward E-Governance (Joseph and Plessis, 2015). To actually ensure adoption of E-Governance benefits at the bottom of the pyramid, powerful marketing is very crucial which would ensure the ultimate use of facilities created, by the citizens (GoI, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…E-government success needs an appropriate information technology infrastructure to support the systems and applications was developed before the e-government program is implemented (Sirat & Komputer, 2013). Besides, previous research by Choi et al (2016), Sorn-In et al (2015), Novita (2014), Al-Shlboul et al (2014), andSirat (2013) showed that infrastructure influences e-government implementation. Hence, referring to previous empirical findings, the second hypothesis to be proposed is as follows: H2: Infrastructure has an effect on e-government implementation in the environment of the Yapen Islands Regency government.…”
Section: Infrastructurementioning
confidence: 91%
“…The study of Thailand's conditions and problems in e-Government development [5] revealed that important and urgent issues to be considered and improved consisted of 1) Policy and direction for Thailand's development of e-Government; 2) Leadership; 3) Infrastructure in information and communication technology; 4) Financial support from the government; 5) Information integration and information exchange between government agencies; 6) Laws and regulations; 7) Government personnel; and 8) Citizens' use of e-Government services.…”
Section: Literature Reviewmentioning
confidence: 99%